Short Term Outcomes of Gamma Knife Radiosurgery for Skull Base Meningiomas in Iran - Bitaraf M. A. Alikhani M.; Shariftabrizi A. (International Journal of Hematology-Oncology and Stem Cell Research, 2005)
Introduction: Skull base meningiomas constitute a large proportion of the meningiomas, which are the most common benign brain tumors. The treatment of skull base meningiomas is specially challenging and controversial due to the proximity of these tumors to the vital brain structures. Radiosurgery is now emerging as an efficient alternative treatment modality which involves the ablation of tumor and the supplying blood vessels by a conformal dose of colliding gamma rays from 201 cobalt-60 sources. Methods: We here report the first 100 meningioma cases treated in Iran using Leksell Gamma knife model C system. Gamma knife treatment was performed by means of 18 grays at 50% isodose. Results: Seventy percent of the total patients referred to the Gamma knife center were skull base men-ingiomas, 40% of patients were new cases of meningioma and the remainder had undergone one or more microsurgery procdeures. There was no mortrality associated with treatment. The most common complications were severe headache (10 patients) and peritumoral brain edema (9 patients). There was 95% tumor control rate as indicated by stable or reduced tumor volume. Conclusion: There was better clinical improvement in new cases relative to those with previous micro-surgery. Our study shows that gamma knife could be considered as primary or adjuvant therapy in all cases of meningioma specially the skull base meningiomas.